STRATEGI PENGEMBANGAN MEDIA RELATIONS DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN MAROS DALAM PELAYANAN INFORMASI KEPADA MASYARAKAT - Adrian Fatwa , Muh; Majid , Abd; Muttaqin Mustari , Andi (UNIVERSITAS MUSLIM INDONESIA, 2022)
This study aims to determine the media relations strategy of Diskominfo in providing information to the public so that the public can find out what the performance of the Maros Regency government is and how the Diskominfo process in providing information services to the people of Maros Regency. The research method used is qualitative and descriptive analysis. This study uses the uses and gratification theory (users and satisfaction) which reveals about the selection of media by users and the satisfaction obtained by users. The results of this study indicate that to provide information services known to Diskominfo using communication strategies through social media Facebook, YouTube, Instagram and the web, while the developments that have been carried out by Diskominfo are by using Planning, Organizing, Mobilizing and Control.